BIVALVIAN DISTRIBUTION PATTERN BASED ON HABITAT CHARACTERISTICS IN THE COASTAL AREA OF LANGSA CITY - Mawardi Mawardi; Fira Yolanda Fira Yolanda; Elfrida Elfrida; Tri Mustika Sarjani (Universitas Islam Negeri Ar-Raniry, 2021)
Bivalves are a class of Phylum molluscs which charaterized by soft, nonsegmented body and protected by a pair of shells. These animals are widespread in coastal areas, especially in mangrove ecosystems. Bivalves are suitable to be used as indicators of aquatic biology because their lives are relatively sedentary and has the ability to respond to water conditions. The purpose of this study was to determine the distribution pattern of Bivalves in the coastal area of Langsa City based on the characteristics of their habitat. Sampling was carried out in March 2021. The method used in this study was the survey method. Determination of the sampling location using the Proposive Sampling method, so that 2 research locations were selected. The collected data was analyzed using the morissita index and dominance index formulas. The results showed that the distribution pattern of Bivalvia in the coastal area of Langsa City was generally classified as a clustered pattern category where the index value of Id>1. The habitat characteristics of the four Bivalvia species are almost the same, namely the texture of the sandy muddy substrate, but different habitat are found for Anadara granosa, namely the sandy muddy texture with the preference of high salinity.